Multi-element doped transparent conductive film and preparation method and application thereof
Through multi-doping technology and magnetron sputtering technology, Sn, W, Mo, Zr, Ti and Ga doped In2O3-based TCO films are prepared under low temperature conditions, solving the problem of low performance of existing TCO films under low temperature conditions, and achieving high performance and high transparency film preparation.
Patent Information
- Application Number
- CN202411696648.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-14
AI Technical Summary
The existing transparent conductive oxide (TCO) films have low performance under low temperature conditions and high carrier concentrations lead to a decrease in near infrared transmittance, limiting their application.
The multi-doping process was used to prepare Sn, W, Mo, Zr, Ti and Ga doped In2O3 targets, and the TCO film was deposited on the glass substrate by magnetron sputtering technology and annealed to improve the electrical properties and transparency of the film.
It realizes the preparation of high-performance TCO films under low temperature conditions, with high electrical properties and transparency, and is suitable for industrial production and promotion applications.
Smart Images

Figure CN119615086A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photovoltaic cells, and in particular relates to a multi-element doped transparent conductive film and a preparation method and application thereof. Background Art
[0002] In recent years, transparent conductive oxide (TCO) films have been widely used in optoelectronic devices such as light-emitting diodes, solar cells, and liquid crystal displays due to their unique properties of low resistivity and high transmittance, and have attracted widespread attention. In2O3-based films have been widely studied, and tin-doped indium oxide (ITO) has been widely studied due to its low resistivity (~10 -4 Ω·cm) and high visible light transmittance (greater than 80%) make it the dominant transparent electrode in the market. However, the high carrier concentration of ITO film will cause the transmittance in the near-infrared region to decrease due to free carrier absorption, thus limiting its application. High-performance TCO film requires low resistivity and high transmittance, but there is a contradiction between the electrical and optical properties of TCO film. Since the resistivity is inversely proportional to the carrier concentration, the higher the carrier concentration, the lower the resistivity; at the same time, the higher the carrier concentration, the higher the free carrier absorption in the film, and the transmittance of the film in the near-infrared region will decrease. The solution is to reduce the carrier concentration of TCO film and increase the mobility of TCO film, so as to obtain TCO film materials with low resistivity and high infrared transmittance.
[0003] People have made a lot of efforts to obtain high-mobility TCO films, and metal doping has been proven to be an effective method. For example, since the standard formation enthalpy of each mole of metal of WO3 and ZrO2 is lower than that of SnO2 and In2O3, and compared with ITO, the addition of Zr and W is expected to increase the formation energy of oxygen vacancies and reduce the concentration of oxygen vacancies. Therefore, compared with ITO films, In2O3-based films doped with a single transition metal (W, Mo, Zr, Ti) element show higher carrier mobility and better near-infrared optical properties. In addition, Ga 3+ Ions can replace In in the In2O3 lattice 3+ Position, and no ionized impurity scattering center is generated, and Ga doping with strong bonding to oxygen atoms can effectively suppress the carrier concentration. However, most of these high-performance TCO films are prepared at high temperatures, which limits their application in devices that require low-temperature processes.
[0004] In order to solve the problem of low performance of transparent conductive oxide films under low temperature conditions, co-doping and multi-doping processes of doping two or more elements into In2O3 have also received increasing attention. Multi-element doping can improve the electrical properties and transparency of transparent conductive oxide films when the process temperature is not so high. Therefore, it is urgent to develop a high-performance transparent conductive oxide film that can be deposited at low temperature. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, an embodiment of the present invention provides a method for preparing a multinary doped transparent conductive film, and the multinary doped transparent conductive film prepared by the method can have high electrical properties and transparency.
[0006] The method for preparing a multi-element doped transparent conductive film according to an embodiment of the present invention comprises the following steps:
[0007] (1) Pretreatment of glass substrate;
[0008] (2) TCO film growth: preparing Sn, W, Mo, Zr, Ti and Ga doped In2O3 targets, and depositing TCO films on the glass substrate pretreated in step (1) using magnetron sputtering technology;
[0009] (3) Annealing the TCO film obtained in step (2).
[0010] The advantages and technical effects brought by the method for preparing a multi-doped transparent conductive film according to the embodiment of the present invention are as follows: 1. The method according to the embodiment of the present invention prepares In2O3 targets doped with Sn, W, Mo, Zr, Ti and Ga, and the elements play a synergistic role, so that the prepared TCO film has higher electrical properties and transparency; 2. The method according to the embodiment of the present invention has a simple preparation process, and the prepared TCO film has good performance, which is convenient for promotion and application in industrial production.
[0011] In some embodiments, in step (1), the pretreatment includes: soaking the glass substrate in acetone, ethanol and deionized water for 10 to 20 minutes respectively, and then drying it with nitrogen.
[0012] In some embodiments, in step (2), the content of Sn in the In2O3 target is 0.01 to 20 wt%, the content of W is 0.01 to 20 wt%, the content of Mo is 0.01 to 20 wt%, the content of Zr is 0.01 to 20 wt%, the content of Ti is 0.01 to 20 wt%, and the content of Ga is 0.01 to 20 wt%.
[0013] In some embodiments, in step (2), the magnetron sputtering technology includes: when the background vacuum of the magnetron sputtering is greater than 1×10 -4 When the pressure is 0.5 Pa, a mixed gas containing argon and oxygen is introduced into the chamber, the manual plug valve is adjusted to maintain the deposition pressure at 0.3-0.5 Pa, and the DC ion source is turned on for magnetron sputtering.
[0014] In some embodiments, the volume content of oxygen in the mixed gas is 1-3%.
[0015] In some embodiments, the temperature of the magnetron sputtering is 22-27° C., the power of the magnetron sputtering is 110-130 W, and the duration is 5-10 min;
[0016] And / or, the mixed gas further contains 0.05-0.3% by volume of hydrogen.
[0017] In some embodiments, the magnetron sputtering has a power of 110 to 130 W and a duration of 5 to 10 minutes.
[0018] In some embodiments, in step (2), the thickness of the TCO film is 90 to 110 nm.
[0019] In some embodiments, in step (3), the annealing temperature is 180-210° C., and the annealing time is 20-40 min.
[0020] The embodiment of the present invention further provides a multi-element doped transparent conductive film, which is prepared by the above-mentioned preparation method.
[0021] An embodiment of the present invention further provides a silicon heterojunction solar cell, comprising the multinary-doped transparent conductive film prepared by the above preparation method or the above multinary-doped transparent conductive film. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is a curve diagram of light transmittance of the TCO films prepared in Example 1 and Example 2;
[0023] Figure 2 It is a curve diagram of the change of the light quantum efficiency of the TCO thin films prepared in Example 1 and Example 2 with wavelength. DETAILED DESCRIPTION
[0024] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0025] The method for preparing a multi-element doped transparent conductive film according to an embodiment of the present invention comprises the following steps:
[0026] (1) Pretreatment of glass substrate;
[0027] (2) TCO film growth: preparing Sn, W, Mo, Zr, Ti and Ga doped In2O3 targets, and depositing TCO films on the glass substrate pretreated in step (1) using magnetron sputtering technology;
[0028] (3) Annealing the TCO film obtained in step (2).
[0029] The method for preparing a multi-doped transparent conductive film in an embodiment of the present invention prepares an In2O3 target material doped with Sn, W, Mo, Zr, Ti and Ga, and the elements play a synergistic role so that the prepared TCO film has higher electrical properties and transparency. The method in an embodiment of the present invention has a simple preparation process, and the prepared TCO film has good performance, which is convenient for promotion and application in industrial production.
[0030] In some embodiments, preferably, in step (1), the pretreatment comprises: soaking the glass substrate in acetone, ethanol and deionized water for 10 to 20 minutes respectively, and then drying it with nitrogen. Pretreatment of the glass substrate can remove surface grease and particulate impurities to ensure the performance of the TCO film deposited on the surface.
[0031] In some embodiments, preferably, in the step (2), the content of Sn in the In2O3 target is 0.01-20wt%, the content of W is 0.01-20wt%, the content of Mo is 0.01-20wt%, the content of Zr is 0.01-20wt%, the content of Ti is 0.01-20wt%, and the content of Ga is 0.01-20wt%.
[0032] In some embodiments, preferably, in step (2), the magnetron sputtering technology includes: when the background vacuum of the magnetron sputtering is greater than 1×10 -4 When the pressure is 0.5 Pa, a mixed gas containing argon and oxygen is introduced into the chamber, the manual plug valve is adjusted to maintain the deposition pressure at 0.3-0.5 Pa, and the DC ion source is turned on for magnetron sputtering.
[0033] In some embodiments, preferably, the volume content of oxygen in the mixed gas is 1-3%, for example, 1%, 1.5%, 2%, 2.5%, 3%, etc.
[0034] In some embodiments, preferably, the temperature of the magnetron sputtering is 22-27°C, for example, 20°C, 23°C, 24°C, 25°C, 26°C, 27°C, etc.; the power of the magnetron sputtering is 110-130W, for example, 110W, 115W, 120W, 125W, 130W, etc.; the duration is 5-10min, for example, 5min, 6min, 7min, 8min, 9min, 10min, etc.
[0035] In some embodiments, preferably, the mixed gas further contains 0.05-0.3% by volume of hydrogen, such as 0.05%, 0.08%, 0.1%, 0.15%, 0.18%, 0.2%, 0.25%, 0.28%, 0.3%, etc. In the embodiment of the present invention, the introduction of hydrogen during the sputtering process can further improve the conductivity of the TCO film.
[0036] In some embodiments, preferably, in the step (2), the thickness of the TCO film is 90 to 110 nm, for example, 90 nm, 95 nm, 100 nm, 105 nm, 110 nm, etc.
[0037] In some embodiments, in step (3), the annealing temperature is 180-210°C, for example, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, and the annealing time is 20-40 min, 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, 21 min, 34 min, 36 min, 38 min, 40 min, etc.
[0038] The embodiment of the present invention further provides a multi-element doped transparent conductive film, which is prepared by the above-mentioned preparation method.
[0039] An embodiment of the present invention further provides a silicon heterojunction solar cell, comprising the multinary-doped transparent conductive film prepared by the above preparation method or the above multinary-doped transparent conductive film.
[0040] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and drawings.
[0041] Example 1
[0042] A 100 nm TCO film is deposited on a glass substrate using a DC magnetron sputtering method. The specific operation method includes the following steps:
[0043] (1) Soak the glass substrate in acetone, ethanol and deionized water for 15 minutes respectively to remove grease and particulate impurities on the surface, and then dry it with nitrogen;
[0044] (2) Preparing an In2O3 target doped with Sn, W, Mo, Zr, Ti and Ga, wherein the content of Sn in the In2O3 target is 2wt%, the content of W is 1.6wt%, the content of Mo is 15wt%, the content of Zr is 5wt%, the content of Ti is 8wt%, and the content of Ga is 18wt%;
[0045] (3) TCO film growth: When the background vacuum of magnetron sputtering reaches 8×10 -4 Pa, introduce a mixed gas containing argon and oxygen into the chamber, adjust the manual gate valve to keep the deposition pressure at 0.45 Pa. Turn on the DC ion source for sputtering process, the deposition temperature is 25 ° C, the volume content of oxygen in the mixed gas is 2%, and it also contains 0.2% of hydrogen by volume, the sputtering power is 120W, and the duration is 7 minutes;
[0046] (4) The deposited film is placed in a high-temperature annealing furnace and annealed at 200°C for 30 minutes in an air atmosphere.
[0047] Example 2
[0048] A 100 nm TCO film is deposited on a glass substrate using a DC magnetron sputtering method. The specific operation method includes the following steps:
[0049] (1) The glass substrate was immersed in acetone, ethanol and deionized water for 15 minutes respectively to remove surface grease and particulate impurities, and then dried with nitrogen gas;
[0050] (2) Preparing an In2O3 target doped with Sn, W, Mo, Zr, Ti and Ga, wherein the content of Sn in the In2O3 target is 5wt%, the content of W is 9wt%, the content of Mo is 7wt%, the content of Zr is 14wt%, the content of Ti is 6wt%, and the content of Ga is 7wt%;
[0051] (3) TCO film growth: When the background vacuum of magnetron sputtering reaches 9×10 -4 When the pressure is 0.045 Pa, a mixture of high-purity argon and oxygen is introduced into the chamber, and the manual gate valve is adjusted to maintain the deposition pressure at 0.45 Pa. The DC ion source is turned on for the sputtering process, the deposition temperature is 20 °C, the volume content of oxygen in the mixed gas is 2%, the sputtering power is 120 W, and the duration is 7 minutes;
[0052] (4) The deposited film is placed in a high-temperature annealing furnace and annealed at 200°C for 30 minutes in an air atmosphere.
[0053] Comparative Example 1
[0054] The preparation method of this comparative example is the same as that of Example 1, except that in step (2), the prepared In2O3 target does not contain Sn and Mo.
[0055] Comparative Example 2
[0056] The preparation method of this comparative example is the same as that of Example 1, except that in step (2), the prepared In2O3 target does not contain Zr and Ga.
[0057] The transmittance of the TCO films prepared in Examples 1 and 2 and Comparative Examples 1 and 2 was tested using a Perkin-Elmer Lambda 950 UV-Vis spectrophotometer. The results are as follows: Figure 1 As shown in Table 1; the mobility, carrier concentration and resistivity of the TCO films prepared in Examples 1 to 2 and Comparative Examples 1 to 2 were tested using the Hall effect of Ecopia HMS-5300 system. The results are shown in Table 1.
[0058] Table 1
[0059]
[0060] Figure 2 The graph of the variation of the light quantum efficiency of the TCO thin films obtained in Example 1 and Example 2 with wavelength is shown in FIG. Figure 2 It can be seen that the current of the TCO film prepared in Example 1 is increased by 1.5% in the medium and long wave range.
[0061] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0062] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.
Claims
1. A method for preparing a multinary doped transparent conductive film, characterized in that: The following steps are involved: (1) Pretreatment of glass substrate; (2) TCO film growth: preparing Sn, W, Mo, Zr, Ti and Ga doped In2O3 targets, and depositing TCO films on the glass substrate pretreated in step (1) using magnetron sputtering technology; (3) Annealing the TCO film obtained in step (2).
2. The method for preparing a multi-element doped transparent conductive film according to claim 1, characterized in that: In the step (1), the pretreatment comprises: soaking the glass substrate in acetone, ethanol and deionized water for 10 to 20 minutes respectively, and then drying it with nitrogen.
3. The method for preparing a multinary doped transparent conductive film according to claim 1, characterized in that: In the step (2), the content of Sn in the In2O3 target is 0.01-20wt%, the content of W is 0.01-20wt%, the content of Mo is 0.01-20wt%, the content of Zr is 0.01-20wt%, the content of Ti is 0.01-20wt%, and the content of Ga is 0.01-20wt%.
4. The method for preparing a multi-element doped transparent conductive film according to claim 1, characterized in that: In step (2), the magnetron sputtering technology includes: when the background vacuum of the magnetron sputtering is greater than 1×10 -4 When the pressure is 0.5 Pa, a mixed gas containing argon and oxygen is introduced into the chamber, the manual plug valve is adjusted to keep the deposition pressure at 0.3-0.5 Pa, and the DC ion source is turned on for magnetron sputtering.
5. The method for preparing a multi-element doped transparent conductive film according to claim 4, characterized in that: The volume content of oxygen in the mixed gas is 1-3%.
6. The method for preparing a multinary doped transparent conductive film according to any one of claims 4 to 5, characterized in that: The temperature of the magnetron sputtering is 22-27° C., the power of the magnetron sputtering is 110-130 W, and the duration is 5-10 min. And / or, the mixed gas further contains 0.05-0.3% by volume of hydrogen.
7. The method for preparing a multi-element doped transparent conductive film according to claim 1, characterized in that: In the step (2), the thickness of the TCO film is 90 to 110 nm.
8. The method for preparing a multi-element doped transparent conductive film according to claim 1, characterized in that: In the step (3), the annealing temperature is 180 to 210° C., and the annealing time is 20 to 40 minutes.
9. A multi-element doped transparent conductive film, characterized in that: The method is prepared by the method according to any one of claims 1 to 8.
10. A silicon heterojunction solar cell, characterized in that: The invention comprises a multinary doped transparent conductive film prepared by the preparation method according to any one of claims 1 to 8 or a multinary doped transparent conductive film according to claim 9.
Citation Information
Cited By
Preparation method of high-mobility SCOT target material
CN120943609A